Proses Personal Selling dalam Pemasaran KPR BCA - Rofian Dedi Susanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The mortgage is one of the excellent facilities from BCA. As a top product, BCA is aggressively offering that facility to its customers. BCA KCU Thamrin offered mortgages through their marketing officer. This study aims to examine and analyze the implementation of a personal selling strategy by BCA KCU Thamrin's marketing officers to achieve the target. This research is descriptive qualitative research with a case study method and the data collection technique uses in-depth interviews. The data analysis is using data reduction, data presentation, and making conclusions. The validity of the data is checked by the source triangulation method. The result of this research shows that the marketing officers of BCA KCU Thamrin strategy for offering mortgages to their customers is by integrating and follow the stages of personal selling strategy, which are Prospecting and Qualifying, Pre approach, Approach, Presentation and Demonstration, Overcoming Objection, Closing the Sale, and Follow Up. The implementation of personal selling strategy viciously has delivered BCA KCU Thamrin to achieve the best of satisfaction score by customers in 49 from 50 (98%). The conclusion that can be drawn is that achieving the best satisfaction score at BCA KCU Thamrin shows the strength of personal selling strategy.